2021
DOI: 10.1016/j.eclinm.2021.101086
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose-escalation single centre clinical trial to evaluate the safety of infusion of memory T cells as adoptive therapy in COVID-19 (RELEASE)

Abstract: Background: Effective treatments are still needed to reduce the severity of symptoms, time of hospitalization, and mortality of COVID-19. SARS-CoV-2 specific memory T-lymphocytes obtained from convalescent donors recovered can be used as passive cell immunotherapy. Methods: Between September and November 2020 a phase 1, dose-escalation, single centre clinical trial was conducted to evaluate the safety and feasibility of the infusion of CD45RA À memory T cells containing SARS-CoV-2 specific T cells as adoptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…Thus, it is also of great importance to establish suitable therapies such as adoptive T cell transfer for cases of insufficient cellular immune response to SARS-CoV-2. In a recent phase 1 clinical trial by Pérez-Martínez and colleagues, the transfer of CD45RA-depleted memory T cell for treatment of hospitalized COVID-19 patients was shown to be feasible and safe ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is also of great importance to establish suitable therapies such as adoptive T cell transfer for cases of insufficient cellular immune response to SARS-CoV-2. In a recent phase 1 clinical trial by Pérez-Martínez and colleagues, the transfer of CD45RA-depleted memory T cell for treatment of hospitalized COVID-19 patients was shown to be feasible and safe ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive T cell therapies have been proven to be an effective treatment approach against malignant tumors and viral infections ( Leen et al, 2006 ). Studies have shown that there were SARS-CoV-2-specific memory T cells in COVID-19 convalescents ( Ferreras et al, 2021 ; Perez-Martinez et al, 2021 ), and the symptoms were significantly improved in patients with SARS-CoV-2 after being treated with SARS-CoV-2-specific memory T cells ( Perez-Martinez et al, 2021 ). This result indicated that adoptive T cell therapies are an effective treatment for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have begun to emerge that demonstrate the potential utility of adoptive transfer therapy using ex-vivo expanded SARS-CoV-2 specific T cells [ 37 , 40 , 41 , 42 , 72 , 73 ]. One of the earliest publications in this context utilized a good manufacturing practice (GMP)-compliant methodology to, in vitro, stimulate and expand virus-specific T cells from convalescent donors using SARS-CoV-2 peptides for the purpose of adoptive immunotherapy aimed at immunocompromised patients exposed to SARS-CoV-2 [ 40 ].…”
Section: T Cell Responses In the Setting Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…One of the earliest publications in this context utilized a good manufacturing practice (GMP)-compliant methodology to, in vitro, stimulate and expand virus-specific T cells from convalescent donors using SARS-CoV-2 peptides for the purpose of adoptive immunotherapy aimed at immunocompromised patients exposed to SARS-CoV-2 [ 40 ]. A subsequent clinical trial demonstrated the safety and feasibility of adoptively transferring purified CD45RA − T cells, which were obtained from SARS-CoV-2 convalescent donors, into partially HLA-matched recipients diagnosed with moderate to severe COVID-19 [ 41 ]. Given that patients with severe COVID-19 are often treated with immune suppressants, ex vivo expanded SARS-CoV-2 specific T cells can be additionally manipulated by CRISPR-Cas9 gene-editing methods to render them resistant to glucocorticoids by inactivating the glucocorticoid receptor gene ( NR3C1 ) [ 42 ].…”
Section: T Cell Responses In the Setting Of Sars-cov-2 Infectionmentioning
confidence: 99%